The association between occupational silica exposure and leukemia: a systematic review and meta-analysis of cohort studies - Jiyuan Shao; Shengchun Wang; Hong Cheng; Pengfei Fu; Xin Zhang (BMC Public Health)
Abstract Respirable crystalline silica is a proven lung carcinogen, but there is limited information of the carcinogenic effects of silica on non-respiratory organs. We aimed to systematically review cohort studies and conduct a meta-analysis to explore the relationship between occupational exposure to silica and the risk of leukemia development. We performed an exhaustive search across three databases (PubMed, Embase, and Web of Science) to identify pertinent cohort studies published since 1987. After removing duplicates and excluding irrelevant studies, 22 studies were included in our analysis. We utilized fixed-effects models in the implementation of our meta-analysis. The combined relative risk of leukemia associated with occupational silica exposure was determined to be 1.11 (95% CI: 0.93–1.33), with no significant differences observed across various industries, geographic regions, exposure periods, or study quality estimates. The present study based on cohort studies provide no evidence that occupational exposure to silica does increase the risk of leukemia.